Philosophy of Science and Social Construction: An Epistemological Study in the Indonesian Context - Yanti, Herina; Ahida, Ridha (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
Exploring the relationship between the philosophy of science and social construction provides a critical foundation for understanding the development of scientific knowledge in modern society, particularly within the Indonesian context. The philosophy of science, which examines the epistemological, ontological, and methodological foundations of scientific inquiry, is influenced by the post-positivist paradigm that emphasizes the role of social factors such as culture and norms in shaping knowledge. Meanwhile, Berger and Luckmann’s theory of social construction views scientific knowledge as the result of social interaction, negotiation, and institutionalization rather than an absolutely objective entity. Using qualitative methods with a content analysis approach and a synthetic examination of sources such as journals, books, and local case studies, this research reveals that scientific knowledge in Indonesia is shaped by local values such as mutual cooperation, post-reform political agendas, and cultural narratives, which often give rise to epistemic bias and the marginalization of traditional knowledge. The key findings highlight practical implications in the fields of education, health, and the environment, suggesting that integrating a decolonial philosophy of science can reduce injustice and support inclusive policies such as the National Health Insurance. Overall, this interdisciplinary approach affirms that scientific knowledge is dynamic and contextual, encouraging critical reflection on absolute objectivity to promote equitable and sustainable development.